Translate or else: marking the glocal troubles of performance research in Croatia - Čale Feldman, Lada (Array, 2009)
This contribution presents various conceptual trajectories of performance in the Croatian theoretical and artistic landscape. The concept of performance left important traces in both of these fields, but the paradigm of performance studies still suffers from institutional dispersion.